PELATIHAN PENULISAN KARYA TULIS ILMIAH (KTI) PADA SISWA SMA AL-MUAYYAD SURAKARTA - Guntur Nugroho; Achmad Mufid Marzuqi; Arini Hidayah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Writing is an activity that is beneficial for both school and university students. Writing activities for students can facilitate the ability to innovate and be creative in expressing ideas or ideas. Scientific Writing (KTI) is one of students' competencies in writing. Mentoring students to write KTI has been carried out at SMU Al Muayyad Surakarta. The implementation of the KTI writing training activities for Al Muayyad High School students went well and received full support from the school. All training activities were attended by trainee students until the end of the activity with an enthusiastic attendance of 100%. In the process of mentoring activities, the participants were enthusiastic to ask questions, share ideas, and express opinions. This activity is an ongoing activity that will involve accompanying teachers to optimize their role in the preparation of scientific papers for students